The Effect of Service Quality and Promotion on Visiting Decisions at Betawi Cultural Villages - Hannan Ghifari; Iskandarsyah Siregar (PT FORMOSA CENDEKIA GLOBAL, 2022)
Broadly speaking, this study aims to determine the effect of service quality and promotion on the decision to visit the Betawi Cultural Village. This study analyzes whether there is an influence of service and promotion on the decision to visit potential tourists. The method used by the author is descriptive qualitative method. While the data collection technique carried out by the author is by interviewing one of the managers of the Betawi cultural village area. The results of this study are that the manager of the Betawi cultural village has provided excellent service, namely by treating visitors in a friendly manner, completing all facilities, not charging an entrance fee, and providing a sense of security and comfort with the services of its employees. Besides that, the promotion that was carried out was quite interesting, namely by using social media